2008
DOI: 10.1097/mao.0b013e3181656998
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Simultaneous Facial Nerve Palsy

Abstract: Bell's palsy is the most common cause of BS-FNP in authors' centers. Although BS-FNP may show more severe paralysis, the overall prognosis in most cases is as good as that in unilateral FNP, excluding life-threatening or traumatic cases. Differential diagnosis is very important because the treatment outcome of BS-FNP depends on the cause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 22 publications
1
21
0
1
Order By: Relevance
“…Bilateral Bell's palsy is rare. 13,14 Currently, no cause for Bell's palsy has been identified. Other conditions may cause facial paralysis, including stroke, brain tumors, tumors of the parotid gland or infratemporal fossa, cancer involving the facial nerve, and systemic and infectious diseases, including zoster, sarcoidosis, and Lyme disease.…”
Section: Introductionmentioning
confidence: 99%
“…Bilateral Bell's palsy is rare. 13,14 Currently, no cause for Bell's palsy has been identified. Other conditions may cause facial paralysis, including stroke, brain tumors, tumors of the parotid gland or infratemporal fossa, cancer involving the facial nerve, and systemic and infectious diseases, including zoster, sarcoidosis, and Lyme disease.…”
Section: Introductionmentioning
confidence: 99%
“…7,9 From another point of view, hypertension is attributed to only 5.4% of acquired facial palsy. 11 In recent years, Kim et al 12 reported bilateral facial nerve palsy in seven cases and defined bilateral simultaneous facial nerve involving both sides of the face within 4 weeks. Our case was not evaluated to be bilateral as there was 8 weeks between two attacks of her complaints.…”
Section: Discussionmentioning
confidence: 99%
“…The condition is characterized by sudden onset of complete or partial facial paralysis that usually occurs overnight 3,4 . The onset of paralysis is accompanied by pain near the mastoid process in majority of the cases along with excess tearing 33%, hyperacusis and dysgeusia.…”
Section: Discussionmentioning
confidence: 99%